The Visnu Purana Ancient Annals of the God with Lotus Eyes - Taylor, McComas (ANU Press, 2021)
Viṣṇu is a central deity in the Hindu pantheon, especially in his manifestation as the seductive cattle-herding youth, Kṛṣṇa. The purāṇas are sacred texts, which, as the Sanskrit name implies, are collections of narratives from 'long ago'. The Viṣṇu Purāṇa is thus an ancient account of the universe and guide to life, which places Viṣṇu-Kṛṣṇa at the centre of creation, theology and reality itself. This text, composed about 1,500 years ago, provides a comprehensive and accessible introduction to the most important themes and narratives that constitute the Hindu imagination: the creation and destruction of the universe, the origin of gods and mortals, the peopling of the world, and the structure and conduct of ideal brahminical society. The Viṣṇu Purāṇa describes the trials of exemplary devotees, the existential struggles between gods and demons, and the exploits of legendary cultural heroes. It also contains many ecstatic songs of praise for the deity. The ever-popular accounts of Kṛṣṇa's love games with the cattle-herding girls of Vṛṇdāvana, which have proliferated in literature, dance, song and visual arts over the millennia, are found here in authoritative form. This faithful yet fluent blank-verse rendering of this great Hindu classic is the first new English translation in nearly 200 years. It will be welcomed by the scholarly community, while remaining readily accessible to a general readership.